The economic dimensions of the new European balances - R. PRODI (PSL Quarterly Review, 2013)
The recent economic and political reforms that have occurred in Eastern Europe have brought with them a realisation that the economic balance in Europe is changing, and that a great deal of industrial investment will be required. Germany will have a key role to play in the new liberated East Europe; however, many economists are very worried that Germany's own economic performance may suffer as a result of taking on these new responsibilities. Both the positive, and possible negative, aspects of these changes are discussed in this article.